Estetrol‐Drospirenone combination oral contraceptive: a clinical study of contraceptive efficacy, bleeding pattern and safety in Europe and Russia. (9th August 2021) - Gemzell‐Danielsson, K; Apter, D; Zatik, J; Weyers, S; Piltonen, T; Suturina, L; Apolikhina, I; Jost, M; Creinin, MD; Foidart, J‐M
Abstract : Objectives: To assess the contraceptive efficacy, bleeding pattern and safety of a combined oral contraceptive containing estetrol (E4) 15 mg and drospirenone (DRSP) 3 mg. Design: Multicenter, open‐label, phase 3 trial. Setting: Sixty‐nine sites in Europe and Russia. Population: Sexually active women aged 18–50 years with regular menstrual cycles and body mass index ≤35 kg/m 2 . Methods: E4/DRSP was administered in a 24 active/4 placebo regimen for up to 13 cycles. Visits were scheduled during Cycles 2, 4, 7 and 10 and after completing treatment during which adverse events (AEs) were collected. Participants recorded medication intake, vaginal bleeding/spotting, use of other contraceptive methods and sexual intercourse on a daily diary. Main outcome measures: Pearl Index (PI) for women 18–35 years (overall and method‐failure), bleeding pattern and AEs. Results: A total of 1553 women aged 18–50 years, including 1353 from 18 to 35 years old, received the study medication. PI was 0.47 pregnancies/100 woman‐years (95% CI 0.15–1.11); method failure PI was 0.29 pregnancies/100 woman‐years (95% CI 0.06–0.83). Scheduled bleeding/spotting occurred in 91.9–94.4% of women over Cycles 1 to 12 and lasted a median of 4–5 days per cycle. The percentage of women with unscheduled bleeding/spotting episodes decreased from 23.5% in Cycle 1 to <16% from Cycle 6 onwards. The most common AEs were headache (7.7%), metrorrhagia (5.5%), vaginal haemorrhage (4.8%) and acne (4.2%). One treatment‐related serious AE was reported, a lower extremity venous thromboembolism. One‐hundred and forty‐one (9.1%) women discontinued study participation because of treatment‐related adverse events. Conclusion: E4/DRSP provides effective contraception, a predictable bleeding pattern and a favourable safety profile. Tweetable abstract: A phase 3 trial with E4/DRSP shows high contraceptive efficacy, a predictable bleeding pattern and favourable safety profile. Tweetable abstract: A phase 3 trial with E4/DRSP shows high contraceptive efficacy, a predictable bleeding pattern and favourable safety profile. This article includes Author Insights, a video abstract available at: https://vimeo.com/bjog/authorinsights16840